A Manual for Tree Nursery Management - Kimondo, James; Kioko, Joseph (Kenya Forestry Research Institute, 2000)
This nursery manual was written to guide the development and management of both public and private tree nurseries. The manual provides practical guidelines for nursery workers, extensionists and farmers. We are confident that it will be a useful reference material for those who have past practical knowledge of raising tree seedlings.
Keywords: FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Forestry